Quality of life of parents of Filipino children with special needs - Gomez, Ivan Neil B.; Gomez, Marie Grace (2013)
Children with special needs (CWSN) experience disability in various areas. The birth of a child with special needs causes stress in the family, most especially among parents, consequently affecting parental quality of life (QOL).

This paper describes the QOL of parents of Filipino CWSN and examined the determinants of parental QOL using a mixed method design. The participants are parents of Filipino CWSN (n=76) and were asked to answer the World Health Organization Quality of Life-Brief (WHOQOL-BREF) Questionnaire Filipino Version. Interviews were also conducted among a sub-sample of the parents who answered the questionnaire earlier (n=6).

Results indicate that parental educational attainment, annual income, child's comorbid conditions and length of time in therapy are the best indicators of parental QOL, as parents of Filipino children with special needs express and exhibit negative stresses that affect their lives.

The researcher recommends family intervention programs that take into account the aforementioned variables and parental advocacy.
Keywords: Quality of life; Parents of children with disabilities